138 Efficacy and Safety of SEP-363856, a Novel Psychotropic Agent with a Non-D2 Mechanism of Action, in the Treatment of Schizophrenia. (April 2020) - Koblan, Kenneth S.; Hopkins, Seth; Kent, Justine; Cheng, Hailong; Goldman, Robert; Loebel, Antony
Abstract: Background: SEP-363856 is a novel psychotropic agent that has shown broad efficacy in animal models of schizophrenia and depression. Its antipsychotic effects appear to be mediated by agonist activity at both trace amine-associated receptor 1 (TAAR1) and 5-HT1A receptors. Notably, SEP-363856 does not bind to any dopaminergic, serotonergic (except 5-HT1A), glutamatergic, or other neuroreceptors thought to mediate the effects of currently available antipsychotics. The aim of this study was to evaluate the efficacy and safety of SEP-363856 in acutely symptomatic patients with schizophrenia. Method: Patients aged 18-40 years meeting DSM-5 criteria for schizophrenia (PANSS total score ≥80) were randomized, double-blind, to 4-weeks of flexible-dose SEP-363856 (50 or 75 mg/d) or placebo. Efficacy measures included the Positive and Negative Syndrome Scale (PANSS) total score (primary), PANSS subscale scores, and the Clinical Global Impressions-Severity (CGI-S) score. Change from baseline in primary and secondary measures were analyzed using a mixed model for repeated measures (MMRM) analysis. Results: Study treatment groups were similar at baseline: SEP-363856 (N=120; male, 64.2%; mean age, 30.0 years; PANSS total score, 101.4) and placebo (N=125; male, 63.2%; mean age, 30.6 years; PANSS total score, 99.7). Least-squares (LS) mean reduction from baseline to week 4 was significantly greater for SEP-363856 vs. placebo on the PANSS total score (-17.2 vs. -9.7; P=0.001; effect size, 0.45), PANSS positive subscale score (-5.5 vs. -3.9; P=0.019; effect size, 0.32), PANSS negative subscale score (-3.1 vs. -1.6; P=0.008; effect size, 0.37), PANSS general psychopathology subscale score (-9.0 vs. -4.7; P<0.001; effect size, 0.51), and the CGI-Severity score (-1.0 vs. -0.5; P<0.001; effect size, 0.52). Discontinuation rates for SEP-363856 vs. placebo were similar overall (21.7% vs. 20.8%) and due to an adverse event (8.3% vs. 6.4%). Change in weight, lipids, glucose and prolactin was similar in SEP-363856 and placebo groups. Adverse events occurring with an incidence ≥2% on SEP-363856 or placebo (with SEP-363856 incidence higher than placebo) were: somnolence (6.7% vs. 4.8%), agitation (5.0% vs. 4.8%), nausea (5.0% vs. 3.2%), diarrhea (2.5% vs. 0.8%), and dyspepsia (2.5% vs. 0%). The proportion of patients who reported any extrapyramidal symptom was 3.3% on SEP-363856 and 3.2% on placebo. Conclusion: In this placebo-controlled study, treatment with SEP-363856, a novel psychotropic agent, was associated with statistically significant and clinically meaningful improvement in schizophrenia symptoms as demonstrated by endpoint change in PANSS total and subscale scores, and CGI-Severity scores. Safety and tolerability findings for SEP-363856 were in general similar to placebo. In particular, SEP-363856 was not associated with extrapyramidal symptoms, akathisia, or hyperprolactinemia, consistent with its non-D2 mechanism of action. ClinicalTrials.gov: NCT02969382 Funding Acknowledgements: Supported by funding from Sunovion Pharmaceuticals Inc.